Undisciplined Heart - Katjavivi, Jane (Book collections on Project MUSE., 2010)
When Jane Katjavivi becomes involved in London in support of change in Southern Africa, she meets and marries a Namibian activist in exile. Moving with him to Namibia at the time of Independence in 1990, she faces a new life in a starkly beautiful country. She starts to publish Namibian writing and opens a bookshop. In Windhoek she develops friendships with a group of strong, independent women, who have also come from other countries, and are engaged in different ways to overcome the divisions of the past. Over coffee, drinks and food, they support each other through times of happiness and sad.